Discovering the Pattern of Pop Song Artist’s Word Formation Processes for Slangs - Sinaga, Yanti Kristina; Herman, Herman; Tannuary, Arwin (Universitas Lancang Kuning, 2022)
Songs is one of the most popular creations of human language, but linguistic study of this medium is still limited. One popular trend is to study the slangs in songs, but previous studies often used a single song or albums with little data, thus this study aims to explore the word formation of slangs in a pop album known for its numerous slangs in each song, namely the album Heaven & Hell by Ava Max. This study is descriptive qualitative research. The data is the lyrics of the 15 songs of the album which were analysed with content analysis to identify the slang word formation processes. Of the total 545 slangs, results found five types of processes: contraction, shortening, blending, clipping and compounding. Contraction is the most dominant type by a huge margin (77%), which is significantly different with the majority of previous studies’ conclusion that clipping is the most dominant type. This study offers a new insight by extending the amount of data. Similar studies in the past have mostly conducted this study on less than 200 data of slangs in a single song or a selection of a few songs in an album, while this study included all 15 songs in an album to obtain more than 500 data and found the pattern of dominant types of slang word formation process to be different than what has been reported over the years.